Activated Carbons for the Adsorption of Vapours from Cigarette Smoke - Peter Branton; Robert H. Bradley (Adsorption Science & Technology)
The main requirements for the adsorption of cigarette smoke vapours using active carbons and the methods currently being used to characterise and select carbons for this application are reviewed. Emphasis is placed on the total volume of smoke, the pulsed characteristics and relatively short challenge times, the compounds in the smoke and the environment in which adsorption takes place. Using experimental data, the types of carbons most suitable for cigarette filter application are considered, as are the adsorption kinetics required to meet this challenge. The concept of carbon ageing and the effects of water within the smoke are also reviewed.